The couch potato - John, Jory (Harper, an imprint of HarperCollinsPublishers, 2020)
"The Couch Potato has everything he needs within reach of his sunken couch cushion. But when the electricity goes out, Couch Potato is forced to peel himself away from the comforts of his living room and venture outside. And when he does, he realizes fresh air and sunshine could be just the things he needs ..."--